A Standardized Lindera obtusiloba Extract Improves Endothelial Dysfunction and Attenuates Plaque Development in Hyperlipidemic ApoE-Knockout Mice - Sang-Hyun Ihm (MDPI AG, 2021)
Lindera obtusiloba extract (LOE), a traditional herbal medicine used to enhance blood circulation and to reduce inflammation, induced NO-mediated endothelium-dependent relaxation, and reduced the formation of reactive oxygen species (ROS). The study investigated whether LOE improves endothelial dysfunction and reduces plaque inflammation and progression by inhibiting ROS generation in a mouse model of atherosclerosis. Eight-week-old apolipoprotein E-deficient (apoE−/−) mice fed with a western diet (WD) were randomized into different groups by administering vehicle (0.5% carboxymethylcellulose (CMC)), LOE (100 mg/kg/day), or losartan (30 mg/kg/day) by gavage until the age of 28 weeks. Fourteen male C57BL/6 mice that were fed normal chow and treated with CMC were used as negative controls. Similar to losartan treatment, LOE treatment induced the concentration-dependent relaxation of aorta rings in WD-fed apoE−/− mice. LOE treatment significantly reduced the vascular ROS formation and expression of NADPH oxidase subunits, including p22phox and p47phox. Compared with WD-fed apoE−/− mice, mice exposed to chronic LOE treatment exhibited reductions in plaque inflammation-related fluorescence signals and atherosclerotic lesions. These effects were greater than those of losartan treatment. In conclusion, LOE treatment improves endothelial dysfunction and reduces plaque inflammation as well as lesion areas by reducing vascular NADPH oxidase-induced ROS generation in a mouse model of atherosclerosis.